Dog bite accidents treated between 2017 and 2018 in a National Hospital in Lima, Peru - Door, Ivanna (2021)
The aim was to describe the epidemiological and clinical characteristics of dog bite accidents treated at Sergio E. Bernales Hospital, located in Comas district in Lima (Peru), between 2017 and 2018. A sheet was prepared in Excel to collect the information from the medical records, 100% of medical records of dog bites was transferred. The variables considered in the study were residence and characteristics of the patient, condition and characteristics of the dog, place of the accident, type of accident, type of and location of the injury, delay in seeking care for the injury and treatment received. Data was processed in STATA 15.0 and summarized using descriptive statistics. Information was collected from 1598 files, 56.4% of the victims were men and most of the victims were between 30 and 59 years old. Accidents caused by runaway stray dogs predominated (39%). Most of the accidents were surprise attacks (94%), with minor injuries (54.8%), and in lower limbs (51.5%). The results are expected to show the effect of this type of accident on human health in order to compel authorities to take preventive measures to alleviate their effects on the population.